Strategies of accessible city for Malaysia as a developing country - Abd Samad, Nur Amirah; Said, Ismail; Abdul Rahim, Asiah (e-International Publishing House, Ltd., UK, 2021)
Becoming an Accessible City in developing countries has mitigating barriers as compared to developed countries. It is comprehensive to nondiscriminate PwDs in access and facilities for equal opportunity. Accessibility legislation of different nations has various success in implementing and enforcing Universal Design through regulatory, government initiatives, and planning approaches. ASEAN developing nations have awareness and advocacy, because the fragmentary built environment, resulting in Accessible City concept that has not strived to expectation. Eliciting from interviews of access consultants and city planning regulations from London, Oslo, and Singapore. Conclusively, extraction of inclusion strategies is to be adapted for implementation in Malaysia.